2015
DOI: 10.1016/j.rboe.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the results from non-arthroplastic treatment (arthroscopy) for shoulder arthrosis

Abstract: ObjectivesTo evaluate the functional results from patients with arthrosis who underwent an arthroscopic procedure, in an attempt to correlate these results with the patients’ epidemiological profile, surgical technique used, possible complications and postoperative protocol.MethodsBetween 1998 and 2011, 31 patients (32 shoulders) with shoulder arthrosis underwent arthroscopic treatment performed by the Shoulder and Elbow Group of the Department of Orthopedics and Traumatology of Santa Casa de São Paulo. Primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In line with literature, we found that longer duration of preoperative complaints was associated with an unfavorable course of SAPS after surgical bursectomy. 20 , 25 , 33 , 36 Interestingly, the peroperative identification of glenoid degeneration was also identified as a negative predictor for patient-reported outcomes after arthroscopic subacromial bursectomy. These results indicate that arthroscopic bursectomy on the nondegenerative shoulder joint results in better patient-reported outcomes compared with the degenerative shoulder.…”
Section: Discussionmentioning
confidence: 97%
“…In line with literature, we found that longer duration of preoperative complaints was associated with an unfavorable course of SAPS after surgical bursectomy. 20 , 25 , 33 , 36 Interestingly, the peroperative identification of glenoid degeneration was also identified as a negative predictor for patient-reported outcomes after arthroscopic subacromial bursectomy. These results indicate that arthroscopic bursectomy on the nondegenerative shoulder joint results in better patient-reported outcomes compared with the degenerative shoulder.…”
Section: Discussionmentioning
confidence: 97%